Structure-based design and biological evaluation of inhibitors of the pseudomonas aeruginosa heme oxygenase (pa-HemO). Issue 6 (1st April 2018) - Liang, Dongdong; Robinson, Elizabeth; Hom, Kellie; Yu, Wenbo; Nguyen, Nam; Li, Yue; Zong, Qianshou; Wilks, Angela; Xue, Fengtian
Graphical abstract: